(untitled) (Scientific journal of the Fergana State University, 2023)
This article analyzes the problem of organizing the continuous practice of students — future teachers of primary education at the university, describing the pedagogical conditions of success and effectiveness of its implementation. The aim of the article is to identify and substantiate the relationship between the creative activity of the student and the continuous practice during the entire period of study at the university. The research problem is the formation and development of professional competence and its components in the process of learning activities of future teachers. It is shown that continuous pedagogical practice has a special role in preparing future teachers of primary classes for professional activity because in the process of its passing students form integral ideas of future pedagogical activity.